PENGARUH PEMBERIAN TEPUNG KIAMBANG (Salvinia molesta) TERHADAP PERFORMA PRODUKSI TELUR DAN EFISIENSI PAKAN PUYUH (Cortunix-cortunix japonica) - Fitria Arbiatur; Tatang Sopandi (FMIPA : Universitas PGRI Adi Buana, 2016)
This study aimed to determine the effect of starch duckweeds (Salvinia molesta) on performance of egg production and feed efficiency quail (Cortunix-cortunix japonica) study was conducted in the village of quail farms Tenaru, District Driyorejo, Gresik for 30 days. The study was conducted experimentally by using a completely randomized design with 6 treatments (0%; 2.5%; 5%; 7.5%; 10%; 12.5% ​​formulation duckweeds flour in the ration, four replications and each replication contained three tails. The results showed that administration duckweeds flour in various formulations of feed rations had no significant effect on the productivity of quail eggs (P> 0.05), but significant effect (P <0.05) on feed intake, feed conversion and feed efficiency quail. Giving duckweeds flour to dose 12.5% ​​increased feed intake amounting to 28.99 grams /quail, feed conversion by 3.08 units, but lower the feed efficiency of 30.14%. Thus the results of research, administration kiambang flour in feed rations are not recommended in livestock quail. Key words: Salvinia (Salvinia molesta), quail (Cortunix-cortunix japonica), Egg Productivity and Efficiency Feed quail